An Investigation of coach behaviors, goal motives, and implementation intentions as predictors of well-being in Sport - Smith, A.; Ntoumanis, Nikos; Duda, J. (Routledge, 2010)
The present study aimed to expand upon Smith, Ntoumanis, and Duda's (2007) research by investigating the influence of coach behaviors and implementation intentions on goal striving in sport. Structural equation modeling analysis with a sample of 108 athletes revealed coach behaviors as predictors of goal motives, which in turn predicted psychological well-being after 8 weeks. Supplementary regression analyses showed no interaction between autonomous goal motives and implementation intentions; however, a synergistic effect was identified for controlled goal motives such that controlled motives furnished with implementation intentions resulted in lower well-being than controlled motives alone. In further analyses, the motives underlying an implementation intention were found to mediate the paths from goal motives to well-being. The findings are discussed in terms of the roles played by goal motives, implementation intentions, and implementation intention motives during goal striving. © Association for Applied Sport Psychology.